Digital technologies in local agri-food systems: Opportunities for a more interoperable digital farmgate sector - Glaros, Alesandros; Thomas, David; Nost, Eric; Nelson, Erin; Schumilas, Theresa (Frontiers in Sustainability, 2023)
Agriculture e-commerce technologies are transforming how small and medium-scale farmers distribute food, consumers access local food, and market vendors negotiate sales. However, most of the social scientific literature exploring digital agriculture concentrates on big data analytics in the context of commodity farming systems and conventional supply chains. In this paper we review the social scientific literature on agriculture e-commerce technologies and situate this literature within broader debates over digital agriculture and its uneven social and economic dynamics. We find that most social scientific literature does not include agriculture e-commerce in its definition of digital agriculture, instead defining it predominantly in terms of production (e.g., variable-rate technology) or verification (e.g., blockchain) technologies. We contextualize this review with results from a series of focus groups exploring the challenges faced by Ontario’s ‘digital farmgate sector’ – the suite of agriculture e-commerce platforms that organize local food sales for hubs, farmers’ markets, and small- and medium-scale farmers –related to lack of platform interoperability. We find that local food systems actors are increasingly adopting e-commerce platforms, particularly in the context of the pandemic, and observing substantial business-related benefits to their adoption. Yet, there are common frustrations with digital tools due to market fragmentation and lack of platform interoperability. We recommend the collaborative development of an open standard for e-commerce platforms that allows for the cross-platform sale of local food and farming products.